1 week 1 story Bulletin of School of Information Science UiTM Sarawak: March - October 2023 - Halamy, Suhaida; Ibrahim, Imilia; Ismaily, Norlida; Salji, Mohd Rafiz; Mohd Jawi, Abdul Ismail; Jamil, Nurul Huda Izzati; Abdul Samad, Sabariah; Sulaiman, Sharin; Zaini, Favilla (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
This bulletin is a success as a result of the cooperation of all parties in contributing information, success stories, and involvement in all activities involving the School of Information Science and UiTM Sarawak, not only at the study center level but also at a higher level, nationally and internationally. The main objective of this One Week One Story publication is to channel information to the activities related to the study center implemented every week throughout the semester. Apart from that, another objective is to encourage creative writing among lecturers to achieve the KPI of the faculty and UiTM. This One Week One Story will be a continuous activity from the School of Information Science in achieving the target of publishing all shared information every semester. The publication of One Week One Story will foster higher excitement and seriousness among all School of Information Science lecturers to write and make publications in the future. Once again, I would like to express my most profound appreciation and CONGRATULATIONS to all the lecturers involved in making the publication of the inaugural Edition of "One Week One Story" a success. Hopefully, the School of Information Science will continue to maintain this excellence.